Penerapan Buku Saku Prasiaga Digital Tema Pelestarian Alam untuk Membentuk Karakter Kemandirian dan Kerjasama Anak di PAUD SPNF SKB Kota Pagar Alam - Susanti, Dian; Suryani, Suryani; Nurlaili, Nurlaili (AT-TUFULA: Islamic Education Early Chilldhood, 2025)
This study aims to analyze the implementation of a digital pre-scouting pocket book themed on nature conservation in shaping the character of independence and cooperation among children at the Non-Formal and Informal Education Development Center (SPNF SKB) Early Childhood Education (PAUD) in Pagar Alam City. Using a qualitative approach with a descriptive method, the research was conducted at the PAUD of SPNF SKB Pagar Alam City. Data were collected through observation, interviews, and documentation, with data validation through triangulation. The findings show that the implementation of the digital pre-scouting pocket book significantly supports the development of children's independence, as evidenced by their ability to complete tasks independently, make simple decisions, and demonstrate initiative in activities. Additionally, cooperation character developed through group-based activities and discussions. The digital pocket book has proven to provide an interactive and meaningful learning experience aligned with the values of scouting education. Supporting factors include teacher support, child engagement, and the attractive design of the book. The challenges encountered include limited digital devices, low teacher digital literacy, and time constraints during implementation.